Doppler Ultrasound Versus Manual Carotid Pulse Palpation for Pulse Detection During Cardiac Arrest: A Prospective Diagnostic Accuracy Study - Ilyas, Muhammed Ahmed; Nadeem, Zainab; Ehtesham ul haq; Shuja Watto, Ahmed; Nawaz Sahi, Qasim; Shoukat Ali Parpia, Salman (Indus Journal of Bioscience Research, 2025)
Background: Accurate detection of carotid pulse during cardiac arrest is critical for guiding resuscitation decisions. Manual palpation is widely used but has known limitations in accuracy and reliability. Doppler ultrasound offers an objective alternative for pulse assessment, though comparative data in real-world settings remain limited. Objective: To compare the diagnostic accuracy of Doppler ultrasound and manual carotid pulse palpation for detecting pulse presence during adult non-traumatic cardiac arrest. Methods: This prospective, single-centre, paired diagnostic accuracy study was conducted in an emergency department in Central Park Teaching Hospital, Lahore. Adult patients (18–75 years) with cardiac arrest undergoing cardiopulmonary resuscitation were enrolled. Each patient underwent paired pulse assessment using Doppler ultrasound and manual palpation during scheduled pulse checks. A composite reference standard incorporating return of spontaneous circulation, end-tidal CO₂, and echocardiographic findings was used. Sensitivity, specificity, predictive values, likelihood ratios, and overall accuracy were calculated and compared using paired statistical methods. Results: Among 161 patients, pulse was present in 19.3%. Doppler ultrasound demonstrated higher sensitivity (93.5% vs 77.4%) and specificity (93.1% vs 85.4%) compared with manual palpation. Overall accuracy was also greater with Doppler ultrasound (93.2% vs 83.9%; p=0.015). Doppler identified pulse more rapidly (mean difference 2.6 seconds, p<0.001) and showed superior inter-operator agreement. Subgroup analyses showed consistent trends favoring Doppler ultrasound. Conclusion: Doppler ultrasound provides more accurate, rapid, and reliable detection of carotid pulse than manual palpation during cardiac arrest. It may serve as a valuable adjunct to standard assessment, particularly in challenging clinical scenarios. Further studies are needed to evaluate its impact on clinical outcomes.